Public finance and revenue mobilization in union parishads - Rahman, Sultan Hafeez; Hossain, Md. Shanawez; Uddin, Mohammed Misbah (BRAC University, 2018)
Despite the long history of local government in Bangladesh, these institutions, particularly Union Parishads (UPs), are heavily dependent on central government grant allocations rather than local revenue. This makes the UPs rely greatly on central government to perform all developmental and operational activities. UPs have little incentive to mobilize their own resources. UPs do not seem to be financially solvent due to lack of capacity and low quality of local human resources, weak tax assessment capacity, concern of elected representatives about losing local political representation, pervasive tax evasion culture, perceived gap between tax payment and service delivery and narrow revenue base. Very few studies have been undertaken to assess the real context and constraints to local resource mobilization at the UP level. This study aims to analyse system and processes to increase revenue from local sources by assessing their capacity as well as challenges.